Cointegration, Error Correction, and Price Discovery on Informationally Linked Security Markets - deB. Harris, Frederick H.; McInish, Thomas H.; Shoesmith, Gary L.; Wood, Robert A. (Journal of Financial and Quantitative Analysis, 1995)
Using synchronous transactions data for IBM from the New York, Pacific, and Midwest Stock Exchanges, we estimate an error correction model to investigate whether each of the exchanges is contributing to price discovery. Johansen's test yields two cointegrating vectors, which together verify the expected long-run equilibrium of equal prices across the three exchanges. Two error correction terms specified as the differences from IBM prices on the NYSE indicate that adjustments maintaining the long-run cointegration equilibrium take place on all three exchanges. That is, IBM prices on the NYSE adjust toward IBM prices on the Midwest and Pacific Exchanges, just as Midwest and Pacific prices adjust to the NYSE.